Development of Android-based health media applications as promotional media in improving COVID-19 preventive behavior in the community - Ira Purnamasari; Ferry Effendy; Dede Nasrullah; Lailatun Ni’mah (Universitas Muhammadiyah Surabaya, 2023)
Corona Virus Disease 2019 (COVID-19) caused by SARS-CoV-2 became a worldwide pandemic. The spread of wrong information causes people to misperceive the information. The massive spread of the virus shows the lack of public knowledge about preventing the transmission of COVID-19. Intrapersonal factors, namely changes in individual behavior, are the main focus of breaking the chain of the spread of COVID-19. This study aims to develop an Android-based health education application for COVID-19 prevention behavior in the community. This research method used an exploratory design with an R&D approach which consists of 2 stages. The first stage was making a prototype application through 1) Evaluation of public knowledge and attitudes about COVID-19 prevention with a questionnaire in the form of a google form to find strategic issues; 2) Development and mapping of prototype content through Focus Group Discussions with nurses and expert consultations. The evaluation used a simple random sampling technique on 193 respondents. The second stage was socialization and application feasibility testing on 193 respondents. The results of the first stage were an overview of the implementation of health education that had not been maximized due to the risk of transmission, sufficient knowledge (52.8%), and negative attitudes (63.2%) toward the prevention of COVID-19, as well as a prototype system of health education in applications that include prevention COVID-19 prevention. It was followed by the second stage of socialization and application feasibility testing for users. This study concludes that the development of an android-based application supports effective health promotion efforts in conveying information to increase knowledge and attitudes toward COVID-19 prevention.